DEVELOPMENT OF INTERACTIVE LEARNING MEDIA BASED ON APPLICATIONS ARTICULATE STORYLINE 3 HUMAN COORDINATION SYSTEM MATERIAL - Nurul Fadhilah H.M; Andi Tenri Ola Rivai; Syamsul (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This research is classified as Research and Development (R&D) and is based on the ADDIE development model, which consists of five stages: Analyze, Design, Develop, Implement, and Evaluate. The study aims to develop learning media and determine its validity, practicality, and effectiveness. The research was conducted at SMA Negeri 2 Takalar, specifically with Class XI Science 1, which consisted of 30 students. The results of the research indicate that the media achieved a validity score of 3.80, categorized as very valid. The practicality assessment showed that teacher responses rated the media at 95.31% and student responses at 85.18%, both categorized as very practical. In terms of learning outcomes, 27 out of 30 students (90%) achieved scores meeting the KKM target, while 3 students (10%) did not. The pretest average score was 28.13, whereas the posttest average score increased to 81.33. The calculated N-gain score was 0.72, which falls into the high category (0.7 ≤ g ≤ 1), indicating a significant improvement in student learning outcomes.